Teaching curricula for musical instruments in Iraq - Abdulhalem Ahmed Hassan (Basrah Arts Journal, 2024)
Every new onset, situation or phenomenon, positive or negative, there are obstacles, obstacles or difficulties you face, or perhaps you need to study more thoroughly and comprehensively including the use of western musical instruments in our eastern Iraqi music. The experience of using Western instruments in the music curriculum in Iraq has played a positive role while at the same time negatively affecting our music heritage in particular. Most music institutes and colleges in Iraq lack the teachers of Arabic authentic instruments such as Al Awd, Al Nai, Al Sinatour and Al Jawah. Because of the lack of a qualified teaching staff who give practical and applied lessons to these machines I have found the opportunity to study quickly this important and useful topic for us and our students, and I am sure I have come up with some indicators or conclusions, some negative and the other positive because it is an experience, we are taking for the first time but it remains the leading and ideal experience and it is sure to evolve in the years ahead.